Biocontrol of Bacterial Wilt Disease Through Complex Interaction Between Tomato Plant, Antagonists, the Indigenous Rhizosphere Microbiota, and Ralstonia solanacearum - Elsayed, Tarek R.; Jacquiod, Samuel; Nour, Eman H.; Sørensen, Søren J.; Smalla, Kornelia (Frontiers in Microbiology, 2020)
Ralstonia solanacearum (Rs, biovar2, race3) is the causal agent of bacterial wilt and this quarantine phytopathogen is responsible for massive loss in several commercially important crops. Biological control of this pathogen is a suitable solution in areas where Rs is endemic. We tested 12 in vitro-selected bacterial antagonists of Rs displaying efficient biological control of wilt symptoms on tomato grown under greenhouse conditions. The population densities of Rs and antagonists were estimated by an integrated strategy coupling selective plating, real-time PCR and fliC gene PCR-Southern blot hybridization in total rhizosphere community DNA. Moreover, we focused on how the Rs-antagonist complex altered the composition of the tomato rhizosphere microbiota via 16S rRNA gene amplicon sequencing. Amongst tested antagonists, Bacillus velezensis (B63) and Pseudomonas fluorescens (P142)-inoculated plants were clean of wilt disease symptoms, accompanied with significant decrease in Rs population compared to non-inoculated controls. The effective biocontrol of Rs populations by antagonists resulted in pronounced shifts in bacterial community compositions, highlighting dynamic taxa responding to Rs and/or inoculants presence and indicating that bacterial competitive niche exclusion and faciliation processes are likely at play. This is supported by confocal laser scanning microscopy visualization of antagonist P-142 colonization patterns via gfp-tagged cells, revealing establishment in lateral roots, root hairs, epidermal cells and within xylem vessels. Both inoculants are promising biological agents for efficient control Rs under field conditions.